Perennial rhizomatous grasses: Can they really increase species richness and abundance in arable land?—A meta‐analysis. Issue 11 (18th September 2020) - Lask, Jan; Magenau, Elena; Ferrarini, Andrea; Kiesel, Andreas; Wagner, Moritz; Lewandowski, Iris
Abstract: Perennial rhizomatous grasses (PRG), such as miscanthus and switchgrass, are considered promising lignocellulosic feedstocks. Their cultivation is expected to experience a significant increase in the near future, as it offers a wide range of benefits. For instance, when PRG replace typical annual crops, positive biodiversity impacts are usually anticipated. However, to date, there is no solid, statistically strong evidence for this hypothesis. This study aims to evaluate its validity through a meta‐analysis based on an extensive systematic literature review of research comparing biodiversity attributes in PRG and common annual crops. Dynamics of species richness and abundance in response to PRG cultivation were quantitatively evaluated drawing on 220 paired comparisons from 25 studies. This includes data on five taxonomic groups—arthropods, birds, earthworms, mammals and plants—and three PRG—miscanthus, switchgrass and reed canary grass. The results indicate that biodiversity tends to be higher in PRG cultivations relative to the reference crops, but the initial hypothesis of significantly beneficial impacts could not be confirmed. Trends were specific to the individual taxonomic groups: significantly higher biodiversity was found for plants and small mammals. Positive but insignificant trends were observed for arthropods and birds, while earthworm response was neutral and insignificant. More substantial conclusions could not be drawn, which is mainly due to the low number of studies conducting biodiversity assessments in PRG cultivations that included a comparison with annual crops. In addition, a detailed analysis of the observed responses was impaired by poor reporting of the parameters influencing biodiversity in the studies reviewed, such as planting and crop density, as well as yields. For this reason, we conclude with a call for improved data reporting in biodiversity assessments of PRG cultivations and detail requirements for future biodiversity research. Abstract : It is commonly hypothesized that the cultivation of perennial rhizomatous grasses (PRG) benefits biodiversity when replacing typical annual crops. However, to date, there is no solid, statistically strong evidence for this hypothesis. This study aimed to deliver a test of its validity. Based on a systematic literature review, a meta‐analysis was conducted. Data on species richness and abundance were extracted from 25 studies. The analysis indicated positive effects on five taxonomic groups (arthropods, birds, earthworms, mammals, plants). However, the positive effects of the cultivation of PRG were not statistically significant.